The tip of the iceberg : spatio-temporal patterns of marine resource confiscations in the Table Mountain National Park - Brill, Gregg Clifford (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2012.